Drivers of Summer Extreme Precipitation Events Over East China. Issue 11 (8th June 2021) - Tang, Yong; Huang, Anning; Wu, Peili; Huang, Danqing; Xue, Daokai; Wu, Yang
Abstract: Extreme summer precipitation often associated with flash floods has devastating impact on the local economies and livelihood of millions of people over East China. Tracking down the drivers of those extreme events will help to understand their formation mechanisms and to improve forecasts. Here the synoptic patterns associated with summer extreme precipitation events over East China during 1961–2018 have been identified systematically and quantitatively using a circulation clustering method. The results show that regional events over East China are dominated by the Eastern Asian summer monsoon associated Meiyu front, landfalling tropical cyclones and low‐pressure vortices. Most sub‐regions have seen increasing trends of extreme rainfall events during the past 6 decades with comparable contributions from the two main drivers. There was a decreasing trend over the North China Plain driven by the low‐level southeasterly winds. Plain Language Summary: Closely linked to flash floods, extreme precipitation is one of the high impacts but low probability weather phenomena that challenge modern numerical predictions. However, models are generally more skillful in predicting synoptic weather systems than precipitation itself. Taking East China as an example, this paper demonstrates the links between extreme precipitation events and synoptic weather systems using circulation clustering. Two major weather systems, the Eastern Asian Summer Monsoon and landfalling tropical cyclones are responsible for most extreme precipitation events (about 70%) over East China during the summer season. If models can accurately predict the strength and position of these weather systems, there may be enhanced potential of predicting regional precipitation extremes. Such implications are not regionally limited. Key Points: The synoptic patterns associated with the summer regional extreme precipitation events over East China during 1961–2018 have been identified Cause of the changes of summer regional extreme precipitation over each subregion of eastern China have been discussed.